KONSEP MOTIVASI PEMBELAJARAN - Almaydza Pratama Abnisa (STAI Asy-Syukriyyah, 2020)
Abstraction Learning motivation is one of the factors that can determine the learning outcomes of students. The existence of learning motivation can provide energy that drives all potential, raises high desire, and increases togetherness which will have an effect on arousing, directing and maintaining student behavior towards the learning environment. Thus the goal of achieving the expected material will be achieved. Therefore learning motivation plays an important role in learning because of several factors: First, learning motivation gives enthusiasm to students in learning activities. Second, learning motivation is a determinant of the kinds of activities that students want to carry out. Third, learning motivation provides instructions for students to behave.